Earth science ([Silver Spring, MD] : Discovery Channel, 2003)
'The Earth Science series provides 61 video clips grouped into three programs which is Earth science I, Earth science II, Space scienc. Earth science I, contains 18 instructional video clips that introduce and explain key topics covering History of the Earth, Fossils/Paleontology, and Mapping the Earth. Earth Science II, contains 24 instructional video clips that introduce and explain key topics covering Volcanoes, Earthquakes, Oceans, and Seasons/Weather/Climate
series 1. Earth science I - series 2. Earth science II - series 3. Space science
Keywords: Earth sciences